Paternal Incarceration and Children's Food Insecurity: A Consideration of Variation and Mechanisms - Turney, Kristen (2014)
Despite growing attention to the unintended consequences of paternal incarceration for children’s wellbeing across the life course, little is known about whether and how paternal incarceration is related to food insecurity among children, an especially acute and severe form of deprivation. In this article, I use data from the Fragile Families and Child Wellbeing Study, a cohort of children born to mostly unmarried mothers, to examine the relationship between paternal incarceration and three indicators of food insecurity among young children: current food insecurity (at age five), onset of food insecurity (between ages three and five), and exit from food insecurity (between ages three and five). Results from the most rigorous modeling strategy, propensity score matching models that further adjust for all covariates, indicate that recent paternal incarceration is associated with an increased risk of current food insecurity, an increased risk of onset into food insecurity, and a decreased risk of exit from food insecurity, but only among children living with fathers prior to his incarceration. Changes in the parental relationship, occurring after the onset of paternal incarceration, explain a moderate portion of these associations. Taken together, these findings highlight the salience of parental relationships in the association between paternal incarceration and children’s food insecurity and have a number of implications for policy